PENGARUH DAYA BELI MASYARAKAT TERHADAP NILAI PENJUALAN IKAN LELE DI DESA GANJARAN KECAMATAN PAGELARAN KABUPATEN PRINGSEWU (Studi kasus pada Kelompok Pembudidaya Ikan Desa Ganjaran Kecamatan Pagelaran Kabupaten Pringsewu ) - Suhardi, Antonius; -, Herlina (Jurnal Manajemen dan Keuangan, 2010)
Purchasing power is purchasing decision to get and use goods and service that influenced income factor, taste, and price likes society need to consuming fish. society taste towards fish lele be society income level description to can fulfil the need so that identify society purchasing power increase. purchasing power positive influential and significant towards fish sale value lele.This watchfulness population 452 fish purchases lele that is got from 3.616 fish purchase total lele divided eight sale periods in fish cultivation group (pokda) glorious bud at regency performance district reward village pringsewu that buys fish lele, while sample is determined as much as 82 respondents that is regency performance district reward village society pringsewu that buy fish lele in pokda glorious bud based on method slovin, as to analyzer that used doubled linear regression. doubled linear regression analysis result shows correlation coefficient (r) as big as 0,616 that demo that fish sale value lele influenced by income, price and taste as big as 37,9%. hypothesis shows f count 15,904 > f table 2,76 or significant 0,000 < 0,05 so ho aversed, analysis from test f show society purchasing power that cover income factor, price and influential taste towards fish sale value lele.Keyword : society purchasing power, sale value